2005
DOI: 10.1002/ijc.21053
|View full text |Cite
|
Sign up to set email alerts
|

Migration‐stimulating factor displays HEXXH‐dependent catalytic activity important for promoting tumor cell migration

Abstract: Like most extracellular matrix (ECM) components, fibronectin (Fn) is proteolyzed generating specific activities. Fibronectin proteinase (Fn-proteinase) represents such a cryptic activity located in the gelatin-binding domain (GBD) of Fn and displays a zinc metalloproteinase activity. The migration-stimulating factor (MSF) is a truncated Fn isoform generated by alternative mRNA splicing and corresponds to the N-terminal part of Fn that comprises the GBD. We show that several human mammary epithelial cells expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 28 publications
1
33
0
Order By: Relevance
“…There is growing evidence suggesting that the TBM is not only a static physical barrier that separates tubular epithelial and interstitial compartments but also a regulator of tubular epithelial cell phenotype and physiology in the kidney (28). For example, a report shows that alterations in TBM composition regulate tubular epithelial cell transdifferentiation in vitro (7,13,18). It is also reported that interstitial collagen type I tends to promote EMT, whereas the collagen type IV is likely to inhibit this phenotypic transition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is growing evidence suggesting that the TBM is not only a static physical barrier that separates tubular epithelial and interstitial compartments but also a regulator of tubular epithelial cell phenotype and physiology in the kidney (28). For example, a report shows that alterations in TBM composition regulate tubular epithelial cell transdifferentiation in vitro (7,13,18). It is also reported that interstitial collagen type I tends to promote EMT, whereas the collagen type IV is likely to inhibit this phenotypic transition.…”
Section: Discussionmentioning
confidence: 99%
“…The TBM consists predominantly of collagen IV and laminin (7,29). It provides a structural foundation for the proper function of tubular epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…It is also expressed during wound healing and strongly overexpressed in a wide range of common human cancers (62,102). rMSF displays a number of potent bioactivities relevant to cancer development processes, including stimulation of cell migration, hyaluronan synthesis (103,104), proteolytic activity (105), and angiogenesis (62,102).…”
Section: Discussionmentioning
confidence: 99%
“…These cells show a bell-shaped dose response with half-maximal activity manifesting at 0.1-1.0 pg/ml, that is, femtomolar concentrations. MSF also stimulates the migration of non-epithelial tumour cells and displays other bioactivities relevant to tumour progression, such as the upregulation of hyaluronan (HA) synthesis, proteolysis, and induction of angiogenesis 20,21,[27][28][29] (unpublished observations). The angiogenic activity of MSF has been demonstrated in both in vitro and in vivo models.…”
Section: Msf: Molecular Characterisation and Diverse Functionalitymentioning
confidence: 96%
“…It is important to note that none of these bioactivities are manifested by any full-length fibronectin isoform, apparently as a consequence of steric hindrance. 31,32 Houard et al 29 have identified a second motif (HEEGH) in MSF module I-8 that seems to mediate the motogenic response of a breast cancer cell line (MCF7) and is additionally required for manifestation of its proteinase activity. Our recent data indicate that the motogenic response of certain target cells may be mediated by both IGD and HEEGH, whereas other cells only respond to the IGD motif.…”
Section: Msf: Molecular Characterisation and Diverse Functionalitymentioning
confidence: 99%